Cardiac MR and CT imaging in children with suspected or confirmed pulmonary hypertension/pulmonary hypertensive vascular disease. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Latus, Heiner; Kuehne, Titus; Beerbaum, Philipp; Apitz, Christian; Hansmann, Georg; Muthurangu, Vivek; Moledina, Shahin
Abstract : Childhood pulmonary hypertension (PH) is a heterogenous disease associated with considerable morbidity and mortality. Invasive assessment of haemodynamics is crucial for accurate diagnosis and guidance of medical therapy. However, adequate imaging is increasingly important in children with PH to evaluate the right heart and the pulmonary vasculature. Cardiac MR (CMR) and computed tomography (CT) represent important non-invasive imaging modalities that may enable comprehensive assessment of right ventricular (RV) function and pulmonary haemodynamics. Here, we present graded consensus recommendations for the evaluation of children with PH by CMR and CT. The article provides a structured approach for the use of CMR and CT imaging, emphasises non-invasive variables of RV function, myocardial tissue and afterload parameters that may be useful for initial diagnosis and monitoring. Furthermore, assessment of pulmonary perfusion and characterisation of the lung parenchyma provides structural information about processes that may cause or be due to PH.